Kontroversi Status Hukum Nikah Mut'ah (Analisis terhadap Pendapat Para Ulama) - May, Asmal (UIN Sunan Kalijaga, 2012)
There are two issues that always actual in Islamic Marriage/Family Law (Munakahat), which until now has always discussed by scholars, because no matter how much people need a clear legal status, ie Marriage Mut'ah and Sirri. Such controversies are appropriately addressed with no preconceived notions, so that it can be studied with a critical attitude and well mannered (no blasphemy). Marriage mut'ah a variant in which marriage is governed by the contested legitimacy of Islam between Sunnis and Shi'ites. In general, the Sunnis consider mut'ah marriage is a type of marriage is not legitimate or illegitimate based on the testimony of hadith, Umar ibn Khattab fatwa and ijma 'Sunni clerics. As for the Shiites, particularly the Shiite Istna 'Ash'arite, consider mut'ah marriage is allowed or lawful, although in practice they diffe r on some of the implementation. This paper presents the analysis about the formulation of opinions about the scholars on the legal status of marriage mut'ah.